2009
DOI: 10.1136/hrt.2009.169078
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of catheter-based treatment of pulmonary atresia and intact ventricular septum

Abstract: The results confirm that percutaneous interventional perforation is an effective first-stage procedure in patients with pulmonary atresia with intact ventricular septum. The right heart appeared to be adequate to maintain a long-term biventricular circulation in the large majority of cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 27 publications
2
31
1
Order By: Relevance
“…RV morphology did not independently correlate to these 2 outcomes. This is contrary to existing studies which have concluded that the TV Z score and bipartite RV morphology was predictive for univentricular palliation and the pulmonary valve Z score was not a dependent variable of ventricular outcome [1,2].…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…RV morphology did not independently correlate to these 2 outcomes. This is contrary to existing studies which have concluded that the TV Z score and bipartite RV morphology was predictive for univentricular palliation and the pulmonary valve Z score was not a dependent variable of ventricular outcome [1,2].…”
Section: Discussioncontrasting
confidence: 95%
“…Typical associated conditions are significant tricuspid insufficiency, variable hypoplasia of the right heart structures, right ventricular hypertrophy, right ventricular dysfunction and obligatory right to left shunting at the atrial level. Prior studies have demonstrated that a bipartite right ventricle (RV) and a tricuspid valve (TV) annulus Z score  -3 are associated with the need for supplemental blood flow to the pulmonary arteries via a surgical Blalock Taussig (BT shunt) and a trend toward subsequent univentricular palliation [1,2] as the RV is unable to support systemic cardiac output. Univentricular palliation includes a second stage bidirectional Glenn anastomosis and finally an intra or extracardiac Fontan palliation procedure.…”
Section: Introductionmentioning
confidence: 99%
“…A number of cutoff points have been suggested in other publications, including a TV annulus of at least 11 mm (19) or a z-score of at least Ϫ3.5 (14,17). In our study, these values appear extremely conservative, but it is important to bear in mind the algorithm with which a z-score is calculated.…”
Section: The Borderline Rvmentioning
confidence: 86%
“…In our study, these values appear extremely conservative, but it is important to bear in mind the algorithm with which a z-score is calculated. Our study has chosen to use the algorithms calculated from the data of Daubeney et al (30), in common with the majority of comparable publications (5,14,16,34,36). However, some studies have used algorithms calculated from autopsy measurements (18,39) or have not made explicit which set of algorithms have been used.…”
Section: The Borderline Rvmentioning
confidence: 98%
See 1 more Smart Citation